Musical Imaginations: Multidisciplinary Perspectives on Creativity, Performance and Perception - Hargreaves, David J.; Miell, Dorothy; Macdonald, Raymond A.R. (Oxford Oxford University Press, 2012)
Musical imagination and creativity are amongst the most abstract and complex aspects of musical behaviour, though, until recently, they have been difficult to subject to empirical enquiry. However, music psychology and some allied disciplines have now developed, both theoretically and methodologically, to the point where some of these topics are now firmly within our grasp. The study of creativity and imagination is growing rapidly in disciplines including psychology, sociology, neuroscience, and education. The inter- and multidisciplinary study of music, and developments in music psychology in particular, mean that studies of musical imagination and creativity in action are now distinctly possible'Musical Imaginations' is a wide ranging, multidisciplinary review of the latest theory and research on musical creativity, performance and perception by some of the most eminent scholars in their respective disciplines. The topics addressed in this book include the investigation of creativity and imagination in music and emotion, composition and improvisation, performance and performance traditions, listening strategies, different musical genres and cultural belief systems, social collaboration, identity formation, and the development of psychologically-based strategies and interventions for the enhancement of performing musicians. With creativity now a topic of significant interest, this book will be valuable to all those in the fields of psychology, sociology, neuroscience, education, as well as to musicians themselves - dealing with practical as well as theoretical issues in music therapy, performance and education. The study of creativity and imagination is growing rapidly in disciplines including psychology, sociology, neuroscience, and education. The inter- and multidisciplinary study of music, and developments in music psychology in particular, mean that studies of musical imagination and creativity in action are now distinctly possible. This book undertakes a multidisciplinary review of these developments. It contains a wide range of contributions by some of the most eminent scholars in their respective disciplines, representing a comprehensive account of the state of the art of theory and research on musical creativity, performance and perception.